The challenges of co-research in labs in real-world contexts: empirical findings from four labs in the context of urban climate-change research. Issue 2 (1st March 2022) - Sieber, Raphael; Faulenbach, Lisa; Fuchs, Marisa; Gülleken, Lisa
Abstract : This article gives insight into two research projects dealing with urban climate change that used laboratories in real-world contexts as a research mode. The article's objective is to investigate the challenges we experienced based on a reflective comparison of the projects' labs. Challenges occurred regarding the lab's core elements, i.e. real-world experiments, the cooperation of scientists and practitioners (transdisciplinarity), the intervention methods (transformation-oriented research), and long-term character and transferability. We suggest that promoting constant communication and reflection, downscaling scope, accepting failure and going beyond the limiting conditions of scientific research may advance the concept of laboratories in real-world contexts.